Beginning the quest law and politics in the early work of Eric Voegelin - Cooper, Barry, 1943- (University of Missouri Press, 2009)
"Examines an analysis of the legal and political writing of Eric Voegelin during the 1920s and the 1930s. Cooper discusses Voegelin's first systematic effort to bring together the principles of philosophical anthropology with his understanding of comparative social science and examines Voegelin's The Authoritarian State and The New Science of Politics"--Provided by publisher.